2003
DOI: 10.1073/pnas.0437846100
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-79 of histone H3 is hypomethylated at silenced loci in yeast and mammalian cells: A potential mechanism for position-effect variegation

Abstract: Methylation of lysine-79 (K79) within the globular domain of histone H3 by Dot1 methylase is important for transcriptional silencing and for association of the Sir silencing proteins in yeast. Here, we show that the level of H3-K79 methylation is low at all Sir-dependent silenced loci but not at other transcriptionally repressed regions. Hypomethylation of H3-K79 at the telomeric and silent mating-type loci, but not the ribosomal DNA, requires the Sir proteins. Overexpression of Sir3 concomitantly extends the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
266
6
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(289 citation statements)
references
References 45 publications
14
266
6
3
Order By: Relevance
“…4A). Strikingly, this is the reverse correlation as previously observed for both H2B-associated ubiquitylation and H3 methylation (Ng et al 2003;Emre et al 2005). Further, we found that telomeric silencing of URA3 cassette expression (Aparicio et al 1991) is dramatically lowered in the ubc9ts strain (data not shown), which may indicate a role of histone sumoylation in promoting telomeric silencing.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…4A). Strikingly, this is the reverse correlation as previously observed for both H2B-associated ubiquitylation and H3 methylation (Ng et al 2003;Emre et al 2005). Further, we found that telomeric silencing of URA3 cassette expression (Aparicio et al 1991) is dramatically lowered in the ubc9ts strain (data not shown), which may indicate a role of histone sumoylation in promoting telomeric silencing.…”
Section: Discussionsupporting
confidence: 71%
“…Telomeric silencing in S. cerevisiae has long been associated with reduced levels of positive-acting histone modifications. This includes low acetylation, maintained through the action of the histone deacetylase Sir2 (Grunstein 1997;Rusche et al 2003), and low ubiquitylation and methylation (Bryk et al 2002;Ng et al 2003), maintained via the histone deubiquitylase Ubp10, which also serves to keep methylation levels low (Emre et al 2005). We detect slightly higher H2B-associated sumoylation at telomeres than at more internal chromosomal sites or at genes (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…We also examined the effects of eliminating Dot1p, an H3K79 histone methyltransferase (38,39). H3K79 methylation is at low levels at yeast telomeres (40), but occurs at high levels at activelytranscribed genes (41). As described below, we found that deletion of SET2 or RPD3 strongly stimulated HIS4 hotspot activity, whereas deletion of HDA1 had a more subtle stimulatory effect.…”
Section: Introductionmentioning
confidence: 79%
“…H3K79 methylation is associated with euchromatin and transcriptional activity (50)(51)(52), but paradoxically loss of H3K79 methylation perturbs heterochromatin formation in budding yeast and mouse cells (51,53). Symmetric methylation of H3R2 is also associated with euchromatin (54).…”
Section: Myc-cse4mentioning
confidence: 99%